Scientific collaboration between Brazil and Spain: journals and citations - Samile Andrea de Souza Vanz (Encontros Bibli, 2016)
Collaboration in science has been studied from different perspectives. At a country level, it is important to determine whether international collaboration improves the quality and visibility of a nation´s output of papers. This study is part of a research work that seeks to map the characteristics of the scientific production of Brazil and Spain and the documents produced in collaboration between them. The objective of the analysis presented here was to establish the importance of collaboration for each country and of the vehicles used for publishing, by observing indicators for the first quartile and citations. The corpus of the research is comprised of publication records that contain at least one Brazilian and Spanish address in the author address field, from 2006 to 2012, in the Web of Science databases. Findings suggest that for Brazil, international scientific collaboration with Spain raises the number of articles published in Q1 journals. Therefore, the country should continue promoting this type of collaboration. For Spain, collaboration with Brazil is not reflected in impact. The increased number of agreements and the incentives given to projects in collaboration between the two countries could expand the quality and visibility of their output.